Penerapan Sistem E-Learning untuk Meningkatkan Produktifitas Kerja Karyawan di Era Pandemi Covid-19 - Muhammad Saifur Rijal; Nida Anisatus Sholihah (STKIP PGRI SITUBONDO, 2022)
E-learning is a training and development delivery system for online education. This system is advantageous in terms of the speed of memory, and the data manipulation capabilities of the computer for greater flexibility in instructions. The purpose of this study are: i) To determine the process of implementing E-learning to increase employee productivity in the Covid-19 pandemic at PT. Asia Talenta Manajemen; ii) To explain E-learning system to increase employee productivity in the Covid-19 pandemic at PT. Asia Talenta Manajemen; iii) To find out the obstacles and constraints obtained from the E-learning system. This research takes a qualitative descriptive approach. The population in this study were all employees of PT. Asia Talenta Manajemen, amounting to 50 people. The sample in this study used the nonprobability sampling method, which is a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as samples, using a purposive sampling approach. The results showed that: (i) E-learning process which is applied at PT. Asia Talenta Manajemen Tangerang provides information or flow that is quite clear and understandable to participants through a fairly long but regular process that is easily understood by employees or E-learning participants. (ii) PT. Asia Talenta Manajemen Tangerang tends to have a positive impact on employees or participants who are involved in training carried out by means of E-learning because participants or employees can implement the skills they have acquired in the available forums as well as in their respective work lines, according to the material presented obtained. (iii) Obstacles and challenges that are obtained from the E-learning system depend on the participants themselves, the participants cannot fulfil the deadline that has been determined, for example, it has been determined that the deadline is one month but the participants cannot fulfil it for up to one year.